Aging-regulated anti-apoptotic long non-coding RNA Sarrah augments recovery from acute myocardial infarction - D. Julia Trembinski (Nature Portfolio, 2020)
Aging induces cardiovascular disease, but which RNA molecules control cardiac aging is poorly understood. Here the authors identified the aging-regulated non-coding RNA Sarrah, which controls cardiomyocyte survival and cardiac function by inducing cardioprotective genes.